2021
DOI: 10.1088/2040-8986/abd887
|View full text |Cite
|
Sign up to set email alerts
|

Spatial coherence effects in second-harmonic generation of scalar light fields

Abstract: We consider the spectral spatial coherence characteristics of scalar light fields in second-harmonic generation in an optically non-linear medium. Specifically, we take the fundamental-frequency (incident) field to be a Gaussian Schell-model (GSM) beam with variable peak spectral density and different coherence properties. We show that with increasing intensity the overall degree of coherence of both the fundamental and the second-harmonic field in general decreases on passage through the non-linear medium. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…We checked that this number ensures the convergence of the results. The procedure for generating the ensemble is analogous to that described in [22] in the spatial domain. In short, a realization is expressed in terms of the HG modes in equation ( 21) with random coefficients and they are required to lead to the coherent-mode representation of equation (20).…”
Section: Construction and Propagation Of Realizationsmentioning
confidence: 99%
See 3 more Smart Citations
“…We checked that this number ensures the convergence of the results. The procedure for generating the ensemble is analogous to that described in [22] in the spatial domain. In short, a realization is expressed in terms of the HG modes in equation ( 21) with random coefficients and they are required to lead to the coherent-mode representation of equation (20).…”
Section: Construction and Propagation Of Realizationsmentioning
confidence: 99%
“…We analyzed this feature and found that the various ensembles effectively imply the same results if the number of realizations N is large and the value N = 500 that we use is sufficient. The analogous property but with spatial domain fields was assessed in [22].…”
Section: Construction and Propagation Of Realizationsmentioning
confidence: 99%
See 2 more Smart Citations